Topical Lidocaine for Chronic Pain Treatment - Voute M; Morel V; Pickering G (Dove Medical Press, 2021)
Marion Voute,1 Véronique Morel,1 Gisèle Pickering1,2 1CHU Clermont-Ferrand, Plateforme d'Investigation Clinique - Centre d'Investigation Clinique, CIC Inserm 1405, Clermont-Ferrand, F-63000, France; 2Université Clermont Auvergne, Inserm 1107, Clermont-Ferrand, F-63000, FranceCorrespondence: Gisèle PickeringCHU Clermont-Ferrand, Plateforme d'Investigation Clinique - Centre d'Investigation Clinique, CIC Inserm 1405, Clermont-Ferrand, F-63000, FranceTel +33 4 73 17 84 16Fax +33 4 73 17 84 12Email gisele.pickering@uca.frAbstract: Topical lidocaine is widely used in current practice for a variety of pain conditions. This literature review shows that its limited absorption and relative lack of systemic adverse events are an attractive analgesic option for a number of vulnerable patients. Topical lidocaine has been approved by health authorities for the treatment of post-herpetic neuralgia in a number of countries, and studies present some degree of evidence of its efficacy and safety in postsurgical pain, diabetic peripheral neuropathy, carpal tunnel syndrome, chronic lower back pain and osteoarthritis. Topical lidocaine may be a great alternative alone or in addition to systemic drugs and non-pharmacological approaches for an optimized pain management and in multimodal analgesia.Keywords: lidocaine plaster, topical, local, neuropathic pain, musculoskeletal pain